Application of Copywriting Strategy in Brodo Active Commercial Video Production - Wirabumi, Arya Wibowo; Nugrahani, Rah Utami; Priastuty, Chairunnisa Widya (PT ARRUS Intelektual Indonesia, 2024)
The creative industry in Indonesia has developed very rapidly, it is shown that the creative economy in Indonesia contributes 7.5% of Indonesia's gross domestic product (GDP). One of the creative industries that is developing very rapidly is the fashion industry. Brodo is a fashion company that was founded in 2010 and initially operated in the leather shoe sector, and now has expanded its reach by having a new section on sports shoes. Brodo itself is one of the companies that has carried out digital marketing to introduce the products they have. One type of digital marketing they have is commercial advertising videos. At the end of 2023, Brodo will launch 2 of their sports shoe products, namely Brodo Mezzala and Inizio Running, which do not yet have an introductory video to market their products in the form of commercial advertising videos. Therefore, the researcher conduct research entitled